PENINGKATAN KINERJA KARYAWAN UNIVERSITAS MUHAMMADIYAH MAGELANG MELALUI KEAKURATAN TUGAS DAN PEMANFAATAN TEKONOLI INFORMASI - Luk, Luk (Universitas Muhammadiyah Magelang, 2007)
The research conducted in Magelang Muhammadiyah University was aimed at knowing the effects of accuracy the tasks of information technology on the employee working performance in Magelang Muhammadiyah University. The independent variables included in this research consisted of accuracy tasks of information technology: Accuracy and Accessibility, the use of information technology involves: Usage Intensity Technology Information and Usage Frequency Technology Information. Working performance for the employees of Magelang Muhammadiyah University was regarded as the dependent variable. The samples were taken by means of a Census Sampling Method within 50 Administration employees of Magelang Muhammadiyah University. 2 double regression analyses were used to proccess the data According to the tests, simultaneously and partially the variables of accuracy, accessibility, usage intensity and usage frequency of Technology Information positively affect the employee working performance. The variable of accuracy is partially a dominant factor enhancing the employee working performance. It is suggested that Technology Information task accuracy should be followed by the Technology Information usage associated to needs to access data and to result information. Supported by Technology Information it is expected that the credibility of Magelang Muhammadiyah University can be enhanced.